Evaluation of left atrial function and mechanical dispersion in breast cancer patients after chemotherapy. Issue 5 (16th March 2022) - Chen, Na; Liu, Ansheng; Sun, Siyao; Wei, Hong; Sun, Qiaobing; Shang, Zhijuan; Sun, Yinghui; Fu, Tingting; Wang, Hongjiang; Xia, Yunlong; Hua, Lanqi; Hsi, David H.; et al.
Abstract: Background: Left atrial (LA) function and mechanical dispersion changes in breast cancer patients treated with chemotherapy remain unclear. Hypothesis: LA function and LA mechanical dispersion in breast cancer patients would be impaired after chemotherapy. Methods: This single‐center retrospective study included 91 consecutive breast cancer patients treated with chemotherapy and 30 controls. Patients were examined by echocardiography three times at intervals. Conventional parameters, left ventricular strain, LA strain, and LA mechanical dispersion were evaluated and compared. Results: LA strain during reservoir phase (LASr), conduit phase (LAScd), and contraction phase (LASct) all decreased markedly after chemotherapy and were lower than those of the controls (all p < .01). The standard deviation of time to peak positive strain during LA reservoir phase corrected by R‐R interval (LA SD‐TPSr) was significantly increased after chemotherapy and was higher than that of the controls ( p < .001). The change of LA function was expressed as Δ. Multivariate linear regression analyses showed that LAVIp (0.399, 95% confidence interval [CI]: 0.610, 1.756, p = .000) was independently associated with ΔLASr, LAPEF (−0.325, 95% CI: −45.123, −10.676, p = .002) and age (0.227, 95% CI: 0.021, 0.350, p = .027) were independently associated with ΔLAScd, and LAVImax (0.341, 95% CI: 0.192, 0.723, p = .001) was independently associated with ΔLASct. LAVImax (0.505, 95% CI: 0.000, 0.001, p = .039) and mitral E (−0.256, 95% CI: 0.000, 0.000, p = .024）were independently associated with ΔLA SD‐TPSr. Conclusions: Mechanical function of LA declined after chemotherapy in breast cancer patients. With the decrease of LA mechanical function, LA mechanical dispersion assessed by two‐dimensional speckle‐tracking echocardiography increased significantly, and its clinical value needs to be further studied.